Dobre praktyki popularyzacji wiedzy o koordynacji systemów emerytalnych w wybranych państwach Unii Europejskiej - Monika Gzik (Ksiegarnia Akademicka Publishing, 2020)
Good Practices to Disseminate Knowledge about Coordination of Pension Systems in Selected European Union Countries. Recommendations for Poland